RETRACTION NOTICE TO ‘‘Determinants of Health Insurance Subscription Among Women of Reproductive Age in Mozambique” [Ahmar Metastasis Health Journal, 2025;4(4): 188-199] - Molelekoa, Thonaeng Charity; Oyekale, Abayomi Samuel (Yayasan Ahmad Mansyur Nasirah, 2025)
This article has been retracted at the request of the Editor in Chief of the Ahmar Metastasis Health Journal, volume 4, number 4, of 2025, pages 188-199, with DOI: 10.53770/amhj.v4i4.357 because it has been published in the Medical and Health Science Journal, volume 9, number 1, year 2025, pages 1-11, with DOI: 10.33086/mhsj.v9i1.6887 and the Universal Journal of Public Health, volume 13, number 2, year 2025, pages 433-443, with DOI: 10.13189/ujph.2025.130215. Papers submitted to AMHJ should neither published previously nor be under consideration for publication another journal. Therefore, the author should make a statement upon submitting. Reusing data in any form must follow good citation principles, therefore this paper has ethical violations in the scientific publishing system.